Peculiarities of the Legal Regulation of a Contract for Work and Labor with Elements of Supply: Theoretical Approaches and Judicial Practice - Alimov, O.T.; Stepanova , T.V. (Bulletin of the Karaganda University “Law Series”, 2025)
This article is devoted to a comprehensive study of the peculiarities of legal regulation of a contract for work and labor with elements of supply within the civil law system of the Republic of Kazakhstan. The relevance of the topic is determined by the complexity of the legal qualification of such mixed contracts and the need to establish criteria for distinguishing between key obligations: the performance of work (contract for work) and the transfer of property (supply) in the context of Kazakhstani legislation, primarily the Civil Code of the Republic of Kazakhstan. Particular emphasis is placed on examining the interrelation and points of intersection of these contracts, as well as on identifying the mechanisms of their correlation and interaction in legal practice. The article analyzes theoretical approaches to identifying the dominant element of the contract for the purpose of subsidiarily applying the relevant legal norms. Particular attention is given to the analysis of judicial practice of the Supreme Court of the Republic of Kazakhstan and local courts in resolving disputes arising from such contractual structures. The study also examines issues related to the allocation of risks, the liability of the parties for improper performance of work or delivery of defective goods, as well as the issues of transfering ownership and the application of provisions on compensation for damages. The findings of the research include reasoned conclusions and recommendations aimed at enhancing legal certainty, unifying approaches in law enforcement practice, and improving the contractual framework in commercial turnover in the Republic of Kazakhstan.